(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
The article mentions the significance of the use of new pedagogical technologies in teaching reading strategies at advanced level and some problems related to improving reading skills are solved by some practical solutions. All abilities,facilities and skills are analyzed for how to be advanced level readers.